Nickel salt modified sulfurized anthryl polymer as well as preparation method and application thereof

By doping and modifying the nickel salt of the anthracene-based polymer to prepare nickel salt-modified anthracene-based polymer, the compatibility and stability problems of the positive electrode materials of magnesium battery are solved, and efficient magnesium ion storage and electrochemical performance improvements are achieved.

CN120484260AActive Publication Date: 2025-08-15HUNAN INSTITUTE OF ENGINEERING
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510982199.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-16
Publication Date
2025-08-15
Estimated Expiration
2045-07-16

AI Technical Summary

Technical Problem

The existing magnesium battery cathode materials have poor compatibility with the electrolyte, resulting in unstable storage process of magnesium ions and short cycle life. The low intrinsic conductivity and easy soluble in the electrolyte limit their energy and power density.

Method used

By doping and modifying the anthracene-based polymer with nickel salt, nickel salt-modified anthracene-based polymer is prepared for use in the positive electrode material of magnesium ion battery to improve its electrochemical performance.

Benefits of technology

It significantly improves the ionic conductivity and cyclic stability of the positive electrode material of magnesium ion battery, improves the diffusion rate and reversibility of Mg2+, extends the cycle life, and improves the electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120484260A_ABST
    Figure CN120484260A_ABST
Patent Text Reader

Abstract

The invention discloses a nickel salt modified sulfurized anthracene-based polymer as well as a preparation method and application thereof. The nickel salt modified sulfurized anthracene-based polymer is obtained by modifying a sulfurized anthracene-based polymer with nickel salt. The preparation method comprises the following steps: directly and fully mixing nickel salt and the sulfurized anthracene-based polymer uniformly, and calcining under the protection of inert atmosphere. The sulfurized anthryl polymer is subjected to simple nickel salt doping modification and is used as a magnesium ion battery positive electrode material, and the electrochemical performance of the magnesium ion battery positive electrode material is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery electrode materials, and in particular relates to a nickel salt-modified anthracene sulfide-based polymer, a preparation method thereof, and an application thereof. Background Art

[0002] Magnesium batteries have been widely used due to their abundant resources, low cost and high volumetric energy density (3833 mAh cm -3 ) and other advantages, it has good application prospects in large-scale battery energy storage systems and has become an ideal next-generation electrochemical energy storage device. However, since the magnesium negative electrode easily reacts with traditional electrolytes and forms non-conductive Mg 2+ The passivation film hinders the Mg 2+ In addition, the positive electrode materials of magnesium batteries have poor compatibility with electrolytes and are not compatible with Mg 2+ The strong electrostatic interaction between the two makes it difficult for magnesium battery energy storage technology to meet practical requirements. Therefore, there is an urgent need to find magnesium battery positive electrode materials that can achieve highly reversible magnesium storage and are compatible with the electrolyte.

[0003] Unlike non-polar cathode materials with rigid structures, which usually require the design of appropriate crystal phase structures to achieve reversible carrier insertion and extraction, organic cathode materials achieve ion storage based on the charge transfer reaction of redox centers, and are therefore not limited by the size and charge of metal ions. At the same time, the intermolecular interaction between organic cathode materials and magnesium ions involved in the reaction is small, making it easy to rearrange bonds and having flexible Mg 2+ migration pathways with low migration barriers, thus achieving high-rate Mg 2+ Storage. In addition, some redox-active organic electrode materials can be obtained from natural substances with low energy consumption. They have the advantages of low cost, high quality energy density, flexible and adjustable structure, and do not rely on scarce transition metal resources, showing great application prospects. However, due to the low intrinsic conductivity of organic molecules and their easy solubility in organic electrolytes, their energy, power density and long-term cycle life are severely limited, which restricts the practical application of organic electrode materials in electrochemical energy storage systems.

[0004] Based on this, Chinese patent CN115975194 B prepared a sulfide-anthracene-based polymer with high sulfur loading, multiple magnesium storage sites and semiconductor properties by fixing redox-active sulfur on a π-conjugated anthracene skeleton to enhance molecular binding force. However, this organic sulfur molecule still faces the following challenges in the magnesium storage process: the large polarization in the first cycle leads to its low coulombic efficiency (about 60%). At the same time, the slow diffusion kinetics inherent in the development of rechargeable magnesium batteries make subsequent cycles unstable and there is capacity loss. Summary of the Invention

[0005] In order to solve the above technical problems, the purpose of the present invention is to provide a nickel salt-modified anthracene sulfide-based polymer and its preparation method and application. By simply doping the anthracene sulfide-based polymer with nickel salt, it can be used as a positive electrode material for magnesium ion batteries, significantly improving its electrochemical performance.

[0006] In order to achieve the above technical objectives, the present invention adopts the following technical solutions: A nickel salt-modified anthracene sulfide polymer, the general structural formula of which is shown in formula (I): (I) is obtained by modifying anthracene sulfide polymer with nickel salt.

[0007] Preferably, the nickel salt is selected from one or more of nickel chloride, bromide, oxalate, nitrate and sulfate.

[0008] It should be noted that the anthracene sulfide polymer in the present invention can be obtained by referring to Chinese patent CN115975194 B, which will not be described in detail here.

[0009] The present invention also provides a method for preparing the nickel salt modified anthracene sulfide polymer, which comprises directly mixing the nickel salt and the anthracene sulfide polymer thoroughly and calcining the mixture under the protection of an inert atmosphere.

[0010] In the present invention, the mixing method can adopt the mixing method commonly used in the prior art, such as stirring mixing, ultrasonic mixing, ball milling mixing, etc., and there is no special requirement.

[0011] Preferably, the mass percentage ratio of the nickel salt to the anthracene sulfide polymer is 0.5-5:95-99.5.

[0012] Preferably, the calcination temperature is 200-300° C. and the calcination time is 2-4 hours.

[0013] The present invention also provides a magnesium battery positive electrode, comprising a current collector and an active material layer coated on at least one side of the current collector; the active material layer comprises the above-mentioned nickel salt-modified anthracene sulfide-based polymer; the nickel salt-modified anthracene sulfide-based polymer, a conductive agent, and a binder are uniformly dispersed in a solvent to form a positive electrode slurry, which is then uniformly coated on the current collector and vacuum dried to obtain the magnesium battery positive electrode.

[0014] Preferably, the mass ratio of the nickel salt-modified anthracene sulfide-based polymer, the conductive agent and the binder is 5~9:1~14:1; the current collector is one of stainless steel, aluminum, copper, nickel-based metal or carbon matrix (such as carbon cloth, carbon paper, etc.); the conductive agent is one of conductive carbon black (such as acetylene black, Ketjen black, Super-P, etc.), conductive graphite (such as KS-6, KS-15, SO, etc.), carbon nanotubes or graphene; the binder is one of a natural binder (such as carboxymethyl cellulose, guar gum, sodium alginate, gum arabic, xanthan gum, etc.) or an artificial binder (such as polyvinylidene fluoride, polytetrafluoroethylene, polyacrylic acid, styrene-butadiene rubber, polyamide, polyvinyl alcohol, poly-3,4-ethylenedioxythiophene / polystyrene sulfonate); and the solvent is one of N-methylpyrrolidone, ethanol and deionized water.

[0015] The present invention also provides a magnesium secondary battery, comprising the above-mentioned magnesium battery positive electrode.

[0016] The present invention has the following beneficial effects:

[0017] 1. The present invention uses anthracene sulfide-based polymer as a positive electrode material for magnesium ion batteries by simple nickel salt doping modification, showing excellent ionic conductivity (1.761×10 -4 S cm -1 ).

[0018] 2. The present invention can expose more Mg by simply doping anthracene sulfide polymer with nickel salt. 2+ The active sites of the reaction, at 1.0 A g -1 Under these conditions, the capacity retention rate of the nickel salt-modified anthracene sulfide-based polymer positive electrode material after 1000 cycles is 98.6% (0.0014% decay per cycle), and the cycle stability is significantly improved.

[0019] 3. The present invention effectively regulates the energy band structure of anthracene sulfide-based polymer by simply doping it with nickel salt, significantly reduces the electron transition energy level, has higher reversibility and smaller electrochemical process polarization (0.79 V), and promotes Mg 2+ The diffusion rate is high, resulting in excellent electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is the cyclic voltammetry curve of the magnesium battery assembled with 2.54% NiCl2-ANS in Example 1, with a scan rate of 2 mV s -1 .

[0021] Figure 2The cyclic voltammetry comparison of the magnesium battery assembled with 2.54% NiCl2-ANS in Example 1 and ANS in Comparative Example 1, with a scan rate of 2.0 mV s -1 .

[0022] Figure 3 The first three charge-discharge curves of the magnesium battery assembled with 2.54% NiCl2-ANS in Example 1 are shown, with a current density of 0.3 A g -1 .

[0023] Figure 4 This is a comparison of the first cycle charge and discharge curves of the magnesium battery assembled with 2.54% NiCl2-ANS in Example 1 and ANS in Comparative Example 1, with a current density of 0.3 A g -1 .

[0024] Figure 5 The comparison of the charge and discharge curves of the second cycle of the magnesium battery assembled with 2.54% NiCl2-ANS in Example 1 and ANS in Comparative Example 1, with a current density of 0.3 A g -1 .

[0025] Figure 6 This is the cycle performance diagram of the magnesium battery assembled with 2.54% NiCl2-ANS in Example 1, with a current density of 0.3 Ag -1 .

[0026] Figure 7 The cyclic voltammetry comparison of the magnesium battery assembled with 2.54% NiCl2-ANS in Example 1 and ANS in Comparative Example 1, with a current density of 1.0 A g -1 .

[0027] Figure 8 This is the rate performance diagram of the magnesium battery assembled with 2.54% NiCl2-ANS in Example 1.

[0028] Figure 9 This is the rate performance diagram of the magnesium battery assembled with 2.54% NiCl2-ANS in Example 1 and the corresponding charge and discharge curves at different rates.

[0029] Figure 10 The cycling performance diagram of the magnesium battery assembled with 2.54% NiCl2-ANS in Example 1 and 0.67% NiCl2-ANS in Example 2, with a current density of 0.3 A g -1 .

[0030] Figure 11 This is the first cycle charge and discharge curve of the magnesium battery assembled with 2.54% NiCl2-ANS in Example 1 and 0.67% NiCl2-ANS in Example 2.

[0031] Figure 12 This is a comparison of the charge and discharge curves of the first cycle of the magnesium battery assembled with 2.54% NiCl2-ANS in Example 1, CoCl2-ANS in Comparative Example 2, and FeCl3-ANS in Comparative Example 3, with a current density of 0.3 A g -1 .

[0032] Figure 13 This is a comparison of the charge-discharge curves of the third cycle of the magnesium battery assembled with 2.54% NiCl2-ANS in Example 1, CoCl2-ANS in Comparative Example 2, and FeCl3-ANS in Comparative Example 3, with a current density of 0.3 A g -1 . DETAILED DESCRIPTION

[0033] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments, but the application and extension of the present invention are not limited.

[0034] The nickel salt modified anthracene sulfide polymer of the present invention is denoted as ANS, wherein AN represents an anthracene ring, S represents a sulfur chain, and the nickel salt is denoted as Ni. 2+ X, X represents chloride ion, bromide ion, oxalate ion or sulfate ion; its general structural formula is shown in formula (I): (Ⅰ).

[0035] The sulfided anthracene-based polymer has a complete conjugated fused-ring anthracene skeleton, wherein each anthracene skeleton unit is connected through a sulfur chain or directly through the carbon of the fused-ring anthracene and is saturated with the sulfur chain. The wavy line in formula (I) represents the connecting bond between each repeating unit, the number of repeating units is 2 to 10, and the sulfur chain is =S=, -S- or -SS-.

[0036] The anthracene skeleton of the above-mentioned sulfided anthracene-based polymer is bonded in different ways and has a structural fragment represented by formula (II): (ⅠⅠ).

[0037] The preparation method of the above-mentioned anthracene sulfide polymer is as follows: After uniformly mixing fused ring anthracene and excess sublimed sulfur, the mixture is placed in a reactor and calcined under an inert atmosphere. The temperature is then raised to continue the reaction to remove excess sulfur, and the mixture is subsequently cooled to room temperature to obtain a black product, namely, anthracene sulfide polymer.

[0038] Example 1

[0039] 1.35 mg of NiCl2 and 50 mg of ANS were uniformly dispersed in anhydrous ethanol and ultrasonically dispersed for half an hour. The NiCl2-containing ANS was then dried overnight in a forced-air drying oven at 80°C to obtain a mixed powder. The mixed powder was then heated to 200°C in argon at a heating rate of 5°C / min for 3 hours to obtain NiCl2-ANS powder. ICP analysis revealed a NiCl2 mass fraction of 2.54 wt% in the NiCl2-ANS powder, designated as 2.54%NiCl2-ANS.

[0040] Example 2

[0041] 0.35 mg of NiCl2 and 50 mg of ANS were uniformly dispersed in anhydrous ethanol and ultrasonically dispersed for half an hour. The NiCl2-containing ANS was then dried overnight in a forced-air drying oven at 80°C to obtain a mixed powder. The mixed powder was then heated to 200°C in argon at a heating rate of 5°C / min for 3 hours to obtain NiCl2-ANS powder. ICP analysis revealed a NiCl2 mass fraction of 0.67 wt% in the NiCl2-ANS powder, designated as 0.67% NiCl2-ANS.

[0042] Comparative Example 1 Anthracene (1 g, 5.6 mmol) and excess sublimed sulfur (5 g, 20 mmol) were ground in an agate mortar for 1 hour. After mixing thoroughly, the mixture was placed in a covered crucible in a tube furnace and heated to 300°C over 1 hour under a stream of nitrogen and held at that temperature for 3 hours to allow for complete reaction. To remove excess sulfur, the mixture was heated to 450°C over 30 minutes and held for 3 hours. The mixture was then cooled to room temperature to yield a black product, anthracene sulfide polymer, designated ANS.

[0043] Comparative Example 2 1.35 mg of CoCl2 and 50 mg of ANS were uniformly dispersed in anhydrous ethanol and ultrasonically dispersed for half an hour. The CoCl2-ANS mixture was then dried overnight in an air drying oven at 80°C to obtain a mixed powder. The mixed powder was then heated to 200°C in an argon atmosphere at a heating rate of 5°C / min and calcined for 3 hours to obtain CoCl2-ANS powder.

[0044] Comparative Example 3 1.35 mg of FeCl₃ and 50 mg of ANS were uniformly dispersed in anhydrous ethanol and ultrasonically dispersed for half an hour. The FeCl₃-ANS mixture was then dried overnight in an 80°C forced air drying oven to obtain a mixed powder. The mixed powder was then heated to 200°C in argon at a heating rate of 5°C / min and calcined for 3 hours to obtain FeCl₃-ANS powder.

[0045] The positive electrode preparation and magnesium battery assembly process are as follows: Each sample was evenly dispersed in N-methylpyrrolidone with the conductive agent acetylene black and the binder polyvinylidene fluoride at a mass ratio of 7:2:1. The mixture was thoroughly ground into a viscous slurry. The slurry was evenly coated on a stainless steel current collector and then vacuum-dried at 110°C for 12 hours to obtain the magnesium battery positive electrode. A polished magnesium metal sheet was used as the negative electrode. 0.4 mol / LMg[B(hfip)₄]₂ / DME was used as the electrolyte. The magnesium battery positive electrode was assembled in a glove box and then used for electrochemical testing. The test voltage range was 0.3-2.8V.

[0046] like Figure 1 As shown, a broad reduction peak was observed at 0.81 V in the first cathodic scan of 2.54% NiCl2-ANS, and two pairs of reversible oxidation peaks were observed at 1.83 / 1.05 V and 1.72 / 1.18 V in the subsequent scans, indicating a reversible (de)magnesiation process of the cathode.

[0047] like Figure 2 As shown in the figure, compared with the blank ANS cathode of comparative example 1, the NiCl2-doped modified ANS cathode exposed more Mg 2+ The active sites of the reaction thus exhibited a higher peak current and smaller polarization (0.79 V).

[0048] like Figure 3 As shown, the 2.54% NiCl2-ANS positive electrode of Example 1 is at 300mA g -1 The first coulombic efficiency at the current density is as high as 87.98%, which is much higher than the 69.5% of the blank ANS positive electrode in comparative example 1 ( Figure 4 The higher average discharge voltage is 1.32 V at 300 mA g -1 Up to 150 mAh g -1 Compared with the blank ANS cathode of Comparative Example 1, the charge-discharge curve of the second cycle of the NiCl2-doped modified ANS cathode shows a smaller polarization ( Figure 5 ), further proved that NiCl2 is an effective additive for ANS cathode, indicating that 2.54% NiCl2-ANS cathode can achieve more stable and reversible magnesium storage during the cycle. At the same time, 2.54% NiCl2-ANS cathode has a high stability and reversible magnesium storage capacity at 0.3 Ag. -1 At a current density of 100 cycles, it still has a capacity of 126.9 mAh g -1 High discharge capacity, capacity retention rate is 94.73% ( Figure 6 ). Compared with the blank ANS cathode of Comparative Example 1, the capacity at 1000 cycles was 68.7 mA g-1 The capacity retention rate is 56.4%, and the 2.54% NiCl2-ANS positive electrode is 1.0 A g -1 After 1000 cycles at a high current density, the discharge capacity can still be maintained at 125.3 mAh g -1 , the capacity retention rate is 98.6%, showing excellent cycle stability ( Figure 7 ).

[0049] like Figure 8 As shown, at current densities of 0.1, 0.3, 0.5, 0.8, 1.0, and 2.0 A g -1 The discharge specific capacities of the assembled magnesium batteries were 148, 136, 130, 125, 123, and 117 mAh g -1 After experiencing 2.0 A g -1 After the extremely high current density is restored to 0.3 A g -1 At a current density of 1000 Å, the capacity can still be restored to the original capacity value, proving that the cathode exhibits good electrochemical stability and reversibility at all test rates. At the same time, the voltage platform and specific capacity of the charge-discharge curves at different current densities during the rate test remain good, further revealing the excellent reversibility and rapid magnesium storage of the cathode in the magnesium storage process ( Figure 9 ).

[0050] like Figure 10 and 11 As shown, after the initial cycle, the 2.54% NiCl2-ANS cathode of Example 1 provided 133 mAhg -1 The reversible discharge capacity and coulombic efficiency of 88% were achieved after 100 cycles, showing a reversible discharge capacity of 127 mAh g -1 The reversible discharge capacity of the positive electrode of Example 2 is 118 mAh g -1 The reversible discharge capacity and coulombic efficiency of 84.5% are achieved.

[0051] like Figure 12 As shown, the 2.54% NiCl2-ANS positive electrode of Example 1 is at 300mA g -1 The first coulombic efficiency at a current density of 1.54% is as high as 92%, which is much higher than the 48% of CoCl2-ANS cathode and 63.7% of FeCl3-ANS cathode. Compared with CoCl2-ANS and FeCl3-ANS cathodes, the charge-discharge curve of the 2.54% NiCl2-ANS cathode in the third cycle shows smaller polarization and higher specific capacity ( Figure 13 ), proving that NiCl2 is an effective additive for ANS cathode and can significantly improve its electrochemical performance.

Claims

1. A nickel salt modified anthracene sulfide polymer, characterized in that: The general structural formula of the nickel salt modified anthracene sulfide polymer is shown in formula (I): (I) is obtained by modifying anthracene sulfide polymer with nickel salt.

2. The nickel salt modified anthracene sulfide polymer according to claim 1, characterized in that The nickel salt is selected from one or more of nickel chloride, bromide, oxalate, nitrate and sulfate.

3. The method for preparing the nickel salt modified anthracene sulfide polymer according to claim 1 or 2, characterized in that: The nickel salt and the anthracene sulfide polymer are directly mixed thoroughly and calcined under the protection of an inert atmosphere to obtain the product.

4. The preparation method according to claim 3, characterized in that The mass percentage ratio of the nickel salt to the anthracene sulfide polymer is 0.5-5:95-99.

5.

5. The preparation method according to claim 3, characterized in that The calcination temperature is 200-300° C. and the calcination time is 2-4 hours.

6. A magnesium battery positive electrode, characterized in that: The invention comprises a current collector and an active material layer coated on at least one side of the current collector; the active material layer comprises the nickel salt-modified anthracene sulfide polymer according to claim 1 or 2 or the nickel salt-modified anthracene sulfide polymer obtained by the preparation method according to any one of claims 3 to 5; the nickel salt-modified anthracene sulfide polymer, a conductive agent, and a binder are uniformly dispersed in a solvent to form a positive electrode slurry, which is then uniformly coated on the current collector and vacuum dried to obtain a magnesium battery positive electrode.

7. The magnesium battery positive electrode according to claim 6, characterized in that: The mass ratio of the nickel salt-modified anthracene sulfide-based polymer, the conductive agent, and the adhesive is 5-9:1-14:1; the current collector is one of stainless steel, aluminum, copper, nickel-based metal, or carbon matrix; the conductive agent is one of conductive carbon black, conductive graphite, carbon nanotubes, or graphene; the adhesive is one of a natural adhesive or an artificial adhesive; and the solvent is one of N-methylpyrrolidone, ethanol, and deionized water.

8. A magnesium secondary battery, characterized in that: Comprising the magnesium battery positive electrode according to claim 6 or 7.

Citation Information

Patent Citations

  • A sulfide anthracene-based polymer and its preparation method and application

    CN115975194B

  • Metal sulfide / conductive polymer composite material and preparation method thereof

    CN110885555A

  • Sulfurized anthryl polymer as well as preparation method and application thereof

    CN115975194A

  • Sodium-ion battery positive electrode material with high cycle performance and preparation method thereof

    CN119480969A

  • Anthraquinone conjugated coordination polymer electrode material for secondary battery as well as preparation method and application of anthraquinone conjugated coordination polymer electrode material

    CN120209337A